Socio-Cultural Change of Society Against Health in the Village of Panciro, Gowa Regency - Ifan Surya Negara (Journal La Sociale, 2020)
This study aims to determine the social and cultural changes of the community towards health in the Village of Panciro, Gowa Regency. This research method uses a qualitative approach and descriptive type. Data sources of this research are interviews and documentation. Activities in data analysis include data reduction, data display, and conclusion drawing. The results showed that traditional treatments or modern treatments can be a comparison in society, but all returned with that choice, in which both have the same goal of treating illness and healing albeit in different ways between the two. There are community norms that are strongly held by the Gowa community where men should not be shaking hands with a woman who is not his mahram (not related by blood), so a woman must be treated by a doctor of the same sex. The Government of Gowa Regency pays attention to the health sector by cutting the administration process to hasten the queue so that this can be a trigger for people to prefer treatment at the hospital rather than traditional medicine.